THE USE OF BIOMIMETIC 2D AND 3D UROTHELIAL IN VITRO MODELS WITH MOLECULAR, MORPHOLOGICAL AND FUNCTIONAL CHARACTERISTICS OF NORMAL AND CANCEROUS BLADDER TISSUE AS AN ALTERNATIVE METHOD IN PRECLINICAL STUDIES (European Journal of Histochemistry)
Advanced in vitro models that mimic the architecture and physiology of human tissues provide a promising alternative to animal testing in preclinical research, in accordance with the 3Rs principle. We developed and validated biomimetic 2D and 3D urothelial models representing both normal and cancerous bladder tissue. These models are based on normal porcine urothelial (NPU) cells, normal human urothelial cells (SV-HUC1), and human bladder cancer cell lines (RT4, T24)1–10. To enhance biomimicry and explore therapeutic potential, we incorporated the human amniotic membrane (hAM) either as a biological scaffold or in the form of processed preparations with potential anticancer effects. The preparation of hAM followed the guidelines of COST Action CA17111.11 Comprehensive structural and functional characterization was performed using live-cell imaging, immunocytochemistry, transmission and scanning electron microscopy, freeze-fracture replica immunolabeling and 3D reconstruction techniques1–10. These models allow for the assessment of cytotoxicity, epithelial barrier integrity, and treatment efficacy under various pathological conditions. Importantly, hAM selectively disrupted the cohesion and structure of cancer spheroids while sparing normal urothelium. These effects were linked to the downregulation of FAK and RhoGTPases, key molecular regulators of cell adhesion and motility. In conclusion, these biomimetic urothelial models closely replicate the molecular and morphological features of human bladder tissue. They offer a reliable, animal-free platform for testing novel therapeutic strategies, including hAM-based interventions, thereby improving translational relevance while adhering to ethical standards.